"Customer Relative as a Mediator: Maximizing Consumer Behavioral Intentions through Service Quality and Corporate Image Gojek Indonesia" - Harisandi, Prasetyo; Yahya, Adibah; Rahmiati, Filda; Yuningsih, Nining; Kusumawati, Hilma (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This study examines the relationships between corporate image, service quality, customer relations, and behavioral intentions among 185 Gojek users in Indonesia. The results indicate positive perceptions of corporate image, service quality, customer relations, and behavioral intentions, with reliability and validity tests confirming strong construct consistency. Service quality was found to significantly influence both customer relations and behavioral intentions, while corporate image did not show a direct effect. Indirectly, service quality positively impacted behavioral intentions through customer relations, highlighting the greater importance of service quality in shaping customer behavior over corporate image